Regional economic and labour market performance and inter-regional labour market balance: the case of Poland - Eugeniusz Kwiatkowski; Leszek Kucharski; Tomasz Tokarski (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2004)
The paper analyses the directions of inter-regional migration in Poland in the years 1995-2002 and points out some major factors that cause the migration. The analyses indicate the voivodships with the largest net migration flows (Mazowieckie, Pomorskie) are characterized by high relative GDP per capita, high labour productivity and high relative wages. In contrast, the voivodships with the smallest net migration flows (Warminsko-Mazurskie, Lubelskie, Swietokrzyskie) are typified by large shares of the employed in agriculture, low labour productivity and wages and low GDP per capita. The size of migration inflows is negatively related to regional unemployment rates. Moreover, the highest propensity for inter-regional migration exhibit young people, aged 21-35, as well as people with tertiary education.
Keywords: 330; regionaler Arbeitsmarkt; regionale Disparität; Wirtschaftsentwicklung; Regionalökonomie; Arbeitsmarktgleichgewicht; Binnenwanderung; regionale Mobilität - Determinanten; Mobilitätsbereitschaft; Bruttoinlandsprodukt; Arbeitsproduktivität; Lohnhöhe; Wirtschaftszweigstruktur; Arbeitslosenquote; berufliche Qualifikation; Dienstleistungsberufe; Lebensalter; demografische Faktoren; soziale Faktoren; Polen